1985
DOI: 10.7567/jjaps.24s2.814
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of La2Ti2O7 by Convergent-Beam Electron Diffraction and Electron Microscopy

Abstract: A convergent-beam electron diffraction study has revealed that the space group of the room temperature phase of La2Ti2O7 is P21. A dark-field electron microscopy has made clear a twinned domain structure in this phase. C BED patterns obtained at above 1053 K were compatible with the space group Cmc21. An incommensurate phase exists between 993 K and 1053 K. The incommensurate reflections are characterized with the vector q̄=((1/2)-δ)ā 0 * from the fundamental reflections of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 2 publications
3
17
0
Order By: Relevance
“…3b). The twin planes are only readily visible in the thicker parts of the crystal away from the edge, as an abrupt change forms at 993 K there is a transition to one or other maximally tilted orientation resulting in the appearance of twin bands noted earlier (Tanaka et al, 1985) and here. Alternatively, both twin types of the monoclinic modification may be represented by slightly different structural forms in the incommensurate phase region, with the transition at 1053 K, not 993 K, determining the final twin distribution at room temperature.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…3b). The twin planes are only readily visible in the thicker parts of the crystal away from the edge, as an abrupt change forms at 993 K there is a transition to one or other maximally tilted orientation resulting in the appearance of twin bands noted earlier (Tanaka et al, 1985) and here. Alternatively, both twin types of the monoclinic modification may be represented by slightly different structural forms in the incommensurate phase region, with the transition at 1053 K, not 993 K, determining the final twin distribution at room temperature.…”
Section: Discussionmentioning
confidence: 91%
“…Our simulations confirmed that, with use of the identical choice of unit cell and orientation, the two twins (or their enantiomorphs) cannot be distinguished by their image contrast alone. However, the change of cell orientation across the twin plane in the experimental image clearly indicates its location.There appears to be no strong structural reason favouring either of the two octahedral layer confor- forms at 993 K there is a transition to one or other maximally tilted orientation resulting in the appearance of twin bands noted earlier (Tanaka et al, 1985) and here. Alternatively, both twin types of the monoclinic modification may be represented by slightly different structural forms in the incommensurate phase region, with the transition at 1053 K, not 993 K, determining the final twin distribution at room temperature.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…These homologs exhibit orthorhombic subcells with similar a-(B5.5 Å ) and c-(B3.9 Å ) parameters, and variable b-parameters that reflect slab thickness and translational symmetry-they are readily distinguished by characteristic diffraction lines below 15 2y: Many A n B n O 3n+2 structures feature sequences of reversible displacive phase transitions associated with cooperative rotations of the [BO 6 ] octahedra [49]. In particular, La 2 Ti 2 O 7 (=La 4 Ti 4 O 14 , n ¼ 4) undergoes the following sequence of reversible tilting phase transitions on cooling [50]: Amam-A2 1 amðincommensurate phaseÞ-P2 1 : For this compound, the Amam-A2 1 am transition is associated with in-phase rotation of octahedra about the c-axis, while the subsequent A2 1 am-P2 1 symmetry reduction (through the incommensurate phase) is caused by octahedral tilting about the long b-axis; the latter transition doubles the c-lattice parameter. A classification scheme that relates the stacking sequences of the {110} perovskitelike layers and octahedral tilt systems to the symmetry of the A n B n O 3n+2 structures has been reported previously [49].…”
Section: La N (Mgti) N O 3n+2 (110) Perovskite-slab Compoundsmentioning
confidence: 98%
“…Below 1.46 a transformation to a defect fluorite structure (with disorder on both cation and anion lattices) is expected while, above 1.78, materials are predicted to adopt a layered perovskite-related (La 2 Ti 2 O 7 ) structure, as shown in Figure 1b. 811 There are four crystallographically distinct types of La and Ti sites in this structure. Materials that exhibit this structural type have been investigated for uses in photocatalysis and electrical applications that exploit their piezoelectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%